23 Psycho-emotional aspects in patients with takotsubo syndrome compared with a control group. (8th December 2021) - Matera, Annalisa; Santoro, Francesco; Mallardi, Adriana; Leopizzi, Alessandra; Vitale, Enrica; Brunetti, Natale Daniele
Abstract: Aims: Takotsubo syndrome (TTS), also called stress cardiomyopathy, is an acute and transient left ventricular systolic dysfunction. Patients affected are usually postmenopausal woman with symptoms similar to myocardial infarction (angina pectoris, shortness of breath, palpitations, etc.) who experienced sudden emotional or physical stress. Emotional stressors are the mayor trigger in about 40% of cases, therefore an evaluation of psychological profile of these patients may have clinical relevance. Evaluate the quality of life, the level of anxiety and depression, the activities of daily life in patients with TTS in comparison with a control group with similar characteristics who haven't developed this pathology. Methods and results: 44 patients were recruited: 22 patients with TTS and 22 patients included in the control-group who didn't develop the syndrome. Patients answered to three questionnaires for the evaluation of daily living activities, (Activities of daily living and Instrumental activities of daily living—ADL and IADL), levels of anxiety and depression (hospital anxiety and depression scale—HADS), and quality of life (36-Item Short Form Health Survey-SF—36). Mean age of the study population was 69 ± 9 years and patients were all female. No differences in term of cardiovascular and no risk factor were found between the two groups. Concerning daily living activities, no differences were present. However, when comparing levels of anxiety and depression, TTS patients had higher levels of anxiety (9.4 ± 5.3 vs. 7.7 ± 4.3; P = 0.3; HADS), meanwhile levels of depression were higher in patients of the control group (6.1 ± 3.4 vs. 6.7 ± 4.7; P = 0.7; HADS). Regarding the quality of life, patients with TTS reported to have reduced energy and had fewer social activities (respectively, 51.2 ± 15.7 vs. 62.8 ± 16.5; P = 0.03; 60.4 ± 29.1 vs. 66.6 ± 30.2 con P = 0.7; SF-36). Conclusions: Patients with Takotsubo syndrome have typical psycho-emotional aspects including higher levels of anxiety and impaired quality of life (as reduced energy and fewer social activities). Further research is needed to better stratify these aspects.